Gender violence against women in universities: Analysis of scientific production (Revista Contexto & Educação, 2024)
This article aims to analyze the scientific production on gender violence against women and initiatives to combat it in the university context. This is a bibliographic review of works indexed in the following databases: Scientific Electronic Library Online (SciELO), Portal de Periódicos Capes and Digital Library of Theses and Dissertations (BDTD), from 2011 to 2021. The study sample is composed of 23 works, from which, from the Content Analysis, three analytical categories emerged: i) Representations and data on gender violence against women in the university context; ii) University initiatives to combat gender-based violence against women, and; iii) Institutionalized policies in universities to combat gender violence against women. The research highlighted the need for universities to create effective policies that aim to prevent gender-based violence against women.
Keywords: gender violence; women; universities; prevention strategies